PATTERNS OF COMMUNICATION OF SUNDA-MINANG INTERETHNIC FAMILIES IN BANDUNG, INDONESIA - Novianti, Evi; Sjoraida, Diah Fatma; Perbawasari, Susie (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
This writing examines inter-ethnic families, from a viewpoint of their communication patterns. The samples in this research are inter-cultural married couples, i.e. Sundanese and Minangkabau background. By descriptive-qualitative method, especially by technique of in-depth interviews, the data from the field shows that inter-ethnic families have a well adaptive attitude. It could be seen from their patterns of communication wether in their communication to their own couples, to their own children, and to their ethnic organizations. It is obvious that there is a meeting between Sundanese and Minangkabau cultures, i.e. each proposes lofty values. Such values are showed in a form of mutual understanding, diversity awareness and acculturated roles and learning. Pattern of communication is an important thing in performing an interethnic family life, for it could resolute the conflict between ethnics and as an openness so that could find the best solution in every problem of life.